1982
DOI: 10.1007/bf01415487
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-ray spectroscopy of89Nb

Abstract: The structure of the N=48 nucleus S9Nb has been studied using in-beam y-ray spectroscopy following a number of reactions. Several levels with spins between 15/2 and 25/2 are identified. The results are discussed in terms of the shell model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1983
1983
1991
1991

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Where more than one decay mode is available for a level, the branching ratios for that level decay are obtained with respect to one of the decay channels with a branching ratio = 1.0 (not shown). The dashed levels correspond to our predictions for the states of unidentified spins at 2.7282 MeV and 2.5237 MeV reported by Diana et al in reference [4] (21/2---,21/2+))=12.1 is obtained in the decay of the 21/2 state. This rules out the observed dipole transition involving this level.…”
Section: Negative Parity Statesmentioning
confidence: 76%
See 2 more Smart Citations
“…Where more than one decay mode is available for a level, the branching ratios for that level decay are obtained with respect to one of the decay channels with a branching ratio = 1.0 (not shown). The dashed levels correspond to our predictions for the states of unidentified spins at 2.7282 MeV and 2.5237 MeV reported by Diana et al in reference [4] (21/2---,21/2+))=12.1 is obtained in the decay of the 21/2 state. This rules out the observed dipole transition involving this level.…”
Section: Negative Parity Statesmentioning
confidence: 76%
“…IV. Diana et al [4], and Fields et al [11], had suggested the possibilities of shell model structures, respectively, for the levels in S9Nb, and for some of the low-lying levels in svy. The latter suggestion came about because of the failure of the quasiparticle-phonon study of Krishan and Sen [8] on avy.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Seniority-three 21/2 + isomers were earlier observed in neighbouring nuclei with N = 50 [6], N = 49 [7][8][9] and N=48 [10]. It seems to be of interest to extend this systematics also to 87y.…”
Section: Introductionmentioning
confidence: 78%
“…In these studies, only a few low-lying states have been assigned J~ values. More recently, states in SgNb have been studied by Diana et al [8] using the 9~ 2n7), 9~ p3nT) and s9y(3He, 3ny) reactions. They have identified and assigned d ~ values to several higher-lying levels.…”
Section: Introductionmentioning
confidence: 98%